Vpliv ukrepov za sanacijo bank na korporacijske predpise - Košar, Jure (Podjetje in delo, 2014)
The financial crisis has demanded an immediate government's response mainly in terms of changes in the banking and public finance laws. The author deals with the influence of both adopted new rules, namely novels J of the Banking Act and the Banking Stability Act, on two fundamental corporate legal acts - the Companies Act and the Takeovers Act.
Keywords: bančništvo; banke; Das Kapital; kapital; management; pravna ureditev; upravljanje; vodenje